Influence of alloy element partitioning on strength of primary α phase in Ti-6Al-4V alloy. Issue 5 (May 2018) - Zeng, L.R.; Chen, H.L.; Li, X.; Lei, L.M.; Zhang, G.P.
Abstract: The partitioning effect of Al (α-phase stabilizer) and V elements (β-phase stabilizer) on strength of the primary α phases in the α/β Ti-6Al-4V alloy with the bimodal microstructure was investigated. It was found that partitioning of Al and V elements took place in the Ti-6Al-4V alloy during the recrystallization process, leading to the variation of the content of Al and V elements in the primary α phases with changing the volume fraction of the primary α phase. Nanoindentation tests reveal a general trend that the strength of the primary α phases increases with decreasing the volume fraction of the primary α phases, and such trend is independent on the loading direction relative to the c -axis of the α phase. The enhanced strength is attributed to the increase of the content of Al element in the primary α phase, but it is not dominated evidently by the change of the V content. The solid solution strengthening contributed from both the elastic strain introduced by the solute atoms and the variation of the density of states was estimated theoretically.